2010
DOI: 10.1111/j.1365-2311.2009.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Host genotype affects the relative success of competing lines of aphid parasitoids under superparasitism

Abstract: 1. In solitary parasitoids, only one individual can complete development in a given host. Therefore, solitary parasitoids tend to prefer unparasitised hosts for oviposition, yet under high parasitoid densities, superparasitism is frequent and results in fierce competition for the host's limited resources. This may lead to selection for the best intra-host competitors. 2. Increased intra-host competitive ability may evolve under a high risk of superparasitism if this trait exhibits genetic variation, and if com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…[42,43]. These phenomena suggest that infection of maternally inherited microorganisms may influence random mating among specific taxa, leading to divergence [39,42,43]. If Wolbachia had a role in population structure observed in the current study has yet to be examined.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[42,43]. These phenomena suggest that infection of maternally inherited microorganisms may influence random mating among specific taxa, leading to divergence [39,42,43]. If Wolbachia had a role in population structure observed in the current study has yet to be examined.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have also found similar phenomena in other species, including Dipteran Drosophila melanogaster [36], Drosophila simulans [37], Rhagoletis cerasi [38], mosquitoes [39], Hemipteran Bemisia tabaci [40,41], and Lepidopteran Danaus chrysippus ( L .) [42,43]. These phenomena suggest that infection of maternally inherited microorganisms may influence random mating among specific taxa, leading to divergence [39,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…But we cannot exclude that there may be genotype‐by‐genotype interactions on fitness‐relevant traits of surviving parasitoids that were not studied here, such as the time until mummification, the rate of emergence from mummies or the body size of emerging parasitoids. In fact, there is some evidence for genotype‐by‐genotype interactions on parasitoid body size (Vorburger et al ., in press). Similarly, we cannot rule out that there may be genotype‐by‐genotype interactions on traits of surviving aphids, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, 2007), which is unlikely to be genotype‐specific. However, Henter & Via (1995) have shown that a resistant and a susceptible clone of the pea aphid did not differ in the number of parasitoid ovipositions they suffered, and Vorburger et al. (in press) found that in A. fabae , up to three quarters of individuals on which parasitoid attacks have been observed may survive.…”
Section: Methodsmentioning
confidence: 99%
“…In general, few markers are available for monitoring the outcome of withinhost competition (but see Goubault et al, 2003;Vorburger et al, 2010). In general, few markers are available for monitoring the outcome of withinhost competition (but see Goubault et al, 2003;Vorburger et al, 2010).…”
Section: Wolmentioning
confidence: 99%